PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN PELANGGAN PADA SPBU 14-202141 MEDAN TENGGARA - Muhammad Rafi Lubis; Rukmini; Toni Hidayat (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2022)
This study aims to determine and analyze the effect of service quality (X1) and facilities (X2) on customer satisfaction (Y) at gas stations 14-202141 Southeast Medan. With a total sample of 96 respondents. The data collection technique is done by using a questionnaire/questionnaire. The analysis used is statistical data analysis using SPSS (Statistic Package for Social Sciences) 24.0 program for windows, namely classical assumption test, multiple linear regression analysis and hypothesis testing. The results of the study indicate that service quality and product quality have a significant effect on customer satisfaction from the results of multiple linear regression Y = 4.003 + 0.328X1 + 0.262X2. To see whether the hypothesis is accepted in this study, it can be seen from the results of hypothesis testing which shows that service quality partially has a positive and significant effect on customer satisfaction at SPBU 14-202141 Southeast Medan, it can be seen from the t-count value (6.010) > t-table (1.66123) and sig (0.000) <0.05 in other words H0 is rejected and H1 is accepted. Likewise with the results of research from the facility variable, which says that the facility partially has a positive and significant influence on customer satisfaction at SPBU 14-202141 Southeast Medan, it can be seen from the t-count value (2.850) > t-table (1, 66123) and sig (0.005) <0.05 in other words H0 is rejected and H2 is accepted. Meanwhile, the quality of service and facilities simultaneously has a positive and significant effect on customer satisfaction at SPBU 14-202141 Southeast Medan, it can be seen from the calculated F value (64.639) > F table (2.70), with a sig level (0.000 ) < 0.05 (5%), in other words H0 is rejected and H3 is accepted. While the level of determination coefficient reaches 0.628, which means that the independent variable in this study has an influence of 62.8% on the dependent variable, while the remaining 37.2 % is influenced by other factors that are not examined